Implementasi Sistem Bagi Hasil Pada Bank Rakyat Indonesia (Bri) Syariah Di Kota Bandar - Yunendra, Stia Aji Cahya; Astuti, Sri Yuli; Alfarezi, Muhammad (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2023)
This study plans to look at the execution of the benefit-sharing framework at Bank Rakyat Indonesia (BRI) Syariah in Bandar Lampung City. The quick advancement of Islamic banking, particularly in correlation with regular banking, shows the high open revenue in monetary foundations that consent to Islamic sharia standards. This exploration utilizes a subjective methodology with interview strategies and writing studies, zeroing in on the utilization of the mutlaqah mudharabah contract for Hajj travel costs. Information examination includes data from Bank BRI Syariah Bandar Lampung Branch and considers factors, for example, BI Rate, bank benefit, bank FDR, and economic situations. The outcomes showed that the benefit-sharing framework at Bank BRI Syariah Bandar Lampung Branch depends on income sharing, whereas benefit sharing depends on all-out income before deducting costs. Bank BRI Syariah sets a base equilibrium standard, and the benefit sharing is changed by the equilibrium. Albeit the benefit-sharing framework enjoys benefits in decency and consistency with sharia standards, the elevated degree of chance in mudharabah and musyarakah support is one of the principal impediments. This examination creates a top-to-bottom comprehension of the execution of the benefit-sharing framework at Bank BRI Syariah, as well as the difficulties and strategies looked at in carrying out Islamic sharia standards in its financial exercises. The discoveries of this exploration give important bits of knowledge to other Islamic monetary establishments and related gatherings to work on the viability and manageability of the Islamic plan of action in Indonesia.